2019
DOI: 10.3390/molecules24071220
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Resveratrol Regulate Intestinal Bacteria and Alleviate Intestinal Inflammation in Weaned Piglets

Abstract: Human infants or piglets are vulnerable to intestinal microbe-caused disorders and inflammation due to their rapidly changing gut microbiota and immaturity of their immune systems at weaning. Resveratrol and curcumin have significant anti-inflammatory, bacteria-regulating and immune-promoting effects. The purpose of this study was to investigate whether dietary supplementation with resveratrol and curcumin can change the intestinal microbiota and alleviate intestinal inflammation induced by weaning in piglets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 57 publications
4
59
0
Order By: Relevance
“…Therefore, appropriate weaning nutrition appears to be essential for enhancing the gut health of animals. Previous studies have shown that some plant extracts (e.g., curcumin, resveratrol and essential oils) had beneficial effects on the performance and intestinal barrier function of mice and weaned piglets [9,30,31]. Currently, garcinol is regarded as one of the most promising plant extracts with effective antioxidant properties [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, appropriate weaning nutrition appears to be essential for enhancing the gut health of animals. Previous studies have shown that some plant extracts (e.g., curcumin, resveratrol and essential oils) had beneficial effects on the performance and intestinal barrier function of mice and weaned piglets [9,30,31]. Currently, garcinol is regarded as one of the most promising plant extracts with effective antioxidant properties [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that plant extract can result in the intestinal flora shift and reduce inflammation, which in turn can improve the intestinal health of piglets [9]. Finally, we used high-throughput sequencing to perform 16S rRNA gene analysis in the colon of piglets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Weaned piglets fed a diet supplemented with curcumin (300 mg/kg of curcumin, mixed with the normal diet) for 28 days, Gan et al demonstrated that this polyphenol was able to alleviate inflammation downregulating the expression of TLR4 by inhibiting Escherichia coli proliferation [123].…”
Section: Curcumin Effects On Gut Inflammationmentioning
confidence: 99%
“…In human clinical trials, it is suggested that the curcumin is effective and can be used in a dosage of 8 g/d [2]. It has been proved that the curcumin revealed many medicinal properties such as antioxidant, antiapoptotic, proliferative properties [3,4], anti-inflammatory [5], anticancer, antitumor activities, and confirmed the protective effects against various diseases [6]. Previous study found that dietary curcumin supplementation had beneficial effects on improving the growth performance of weaned pigs [7].…”
Section: Introductionmentioning
confidence: 96%